Digital queer: identitas komunikasi genderqueer selebgram Mimi Peri - Pradhuka, Briant Nor; Utari, Prahastiwi; Sudarmo, Sudarmo (Jurnal Studi Komunikasi, 2020)
Ahmad Jaelani, an Instagram influencer who adopted Mimi Peri as their new identity, plays a significant role in the emergence of digital queer phenomena in Indonesian cyber society. Ahmad Jaelani triggered the digital queer phenomena when he came out as gender queer. Jaelani’s brave act to adopt Mimi Peri identity resulted from various identity struggle. Before conforming to his new identity, he went through several stages, such as identity confusion, identity comparison, identity tolerance, identity acceptance, identity pride, and finally identity synthesis. He conveys his new identity through innovation and creativity, which are presented in several layers, such as personal layers, enactment layers, relational layers, and communal layers.